Análisis estilístico de la obra trece relatos de César Dávila Andrade - Marin Alejandro, Jessica Maribel (2016)
The thesis entitled “ANÁLISIS ESTILÍSTICO DE LA OBRA “TRECE RELATOS” DE CÉSAR DÁVILA ANDRADE”, it was proposed the following general objective; to convey the literary figures in the work "Thirteen Stories" by César Dávila Andrade. The methodology was qualitative in nature, using the following methods: inductive method, deductive, analytical, synthetic, and hermeneutic bibliographic technique. In the literary analysis, the following results were obtained: the stories of the 1930s have a vast style of lyricism, realism and naturalism; literary figures that were found are: logical figures (convinced), picturesque (described) and pathetic (shaking); the most recurrent figures are: antithesis, parallelism prosopopeyas, portraits, prosopografía, exclamation, onomatopoeia, anaphora, simile, images, asíndeton, polisíndeton, symbol, epithets; language tropológico as metaphors, images. In the conclusions summarized that the term daviliana is its constant search of the death as the only way to happiness, and poetry narrative as permanent space of exile incomprehension of a world that does not feel belong. The recommendations are addressed to the public reader, that perform different studies to work studied, from other points or literary trends and highlight the action of our writer Cesar Davila that by his passion of the letters we located the heart in the gangrene of the humanity.